Does foreign direct investment contribute to reducing unemployment in Algeria? - Mohammed DAOUDI (Theoretical and Applied Economics, 2023)

(untitled)
The article attempts to show the impact of foreign direct investment on the unemployment rate in Algeria with the integration of the following variables into the model, real gross domestic product, gross fixed capital formation and public spending. The model variables were chosen on the basis of economic literature and previous studies. These annual data cover the period from 1980 to 2020, using ARDL model and Toda-Yamamoto causality. Through the applied results that we obtained based on the approved model, whether in the long or short term, or through causal relationships, foreign direct investment does not contribute to reducing unemployment rates in Algeria.